Determining the Concept and Structure of Forensic Characteristics of Murders Committed in Connection with Domestic Violence - K. А. Shapoval (Law and Safety)
Ukraine continues to work actively to combat domestic violence. The most serious crime that can be committed in this direction is murder, which was preceded by all kinds of domestic violence. There are innovations in criminal law aimed at protecting people from domestic violence. However, murders committed in connection with its use are not legally separated into a certain group of murders and have no qualifying features. In particular, there is no forensic characteristic of murders committed in connection with domestic violence.